Optimization tool for EV-transmissions - Barreng, Anton (My University, 2018)
Due to the increasing concern for fossil fuel powered vehicles negative impact on the environment car manufacturers are looking more and more towards alternative drivetrains. One of the solutions is to use an electric motor also known as an e-machine. To be able to utilize an e-machine efficiently a transmission is needed between the e-machine and the driveshafts connecting to the wheels. The design process for this type of transmission is not as well mapped out as for a conventional transmission. The aim of the thesis work was to create a tool that aids the initial part of the design process. Matlab programing language was used to create a program that uses the basic parameters known in the start of a transmission project to provide a recommendation on where initial development should be started. The tool provides a variety of solutions ranked by different criteria selected by the user. The program is function based, starting by creating 2D layouts, calculating gear widths and progressing by calculating bearing forces and bearing sizes. Since the aim of the tool was to provide a quick estimation of the optimal layout, simplified calculations were used in the function files. The accuracy was verified using two methods in the Masta transmission program and the result showed that the transmissions recommended by the tool are optimized.
Keywords: Transport; Hållbar utveckling; Maskinteknik; Farkostteknik; Transport; Sustainable Development; Mechanical Engineering; Vehicle Engineering